Exploiting Induced skin electric potential for body-area IoT system functions - Yan, Zhenyu (Nanyang Technological University, 2020)
Internet-of-Things (IoT) devices are increasingly deployed in indoor environments. In particular, there will be an IoT device proliferation in the household settings. For instance, it is estimated that by 2022, a typical family home could contain more than 500 smart devices. IoT devices are penetrating the industry environments to enable the realization of Industry 4.0. IoT devices are generally equipped with processing units, various sensors, communication modules, and software platforms to meet the application needs. A key characteristic of the IoT systems is the heterogeneity of hardware and software. Specifically, there are numerous IoT hardware platforms with diverse specifications and a number of embedded IoT operating systems (OSes) such as Android Things, Wear OS, Contiki, and Arduino. Such heterogeneity introduces significant challenges to the implementation of various basic system functions, such as clock synchronization and device authentication. Clock synchronization aims at keeping the clocks of the IoT devices under consideration having the same value all the time. However, the design of clock synchronization faces the trade-off between the synchronization accuracy and the universality over a variety of platforms. Specifically, high synchronization accuracy generally requires platform-dependent hardware-level network packet timestamping, which may not be available on any IoT platform. Thus, designing clock synchronization approaches to improve the Pareto frontier of accuracy versus universality is of great research interest. Device authentication verifies whether a device has a certain property (e.g., possession of a secret key). It can be used to manage the accesses to IoT devices. However, the existing device authentication approaches require cumbersome sensor hardware or user’s manual input. Thus, they are devised for specific devices and are generally inapplicable to a range of heterogeneous IoT devices.